Peran dan Tanggung Jawab Lembaga Penjamin Simpanan dalam Penanganan dan Penyelamatan Bank Gagal Berdampak Sistemik - Inda Rahadiyan (Fakultas Hukum Universitas Islam Indonesia, 2016)
The problem of this research is related to the roles and responsibilities of Deposit Insurance Agency (LPS) in handling and rescuing Bank Mutiara as a failed bank leading to systemic effects. This research used empirical legal method. The findings show that the management and rescue of Bank Mutiara was done by LPS by conducting temporary capital investment. At the final stage of the rescue process, LPS conducted share divestment of Bank Mutiara to J. Trust Ltd as a potential investor by making agreement of conditional purchase and sale of share.